Pengenalan Pengelolaan Obat Rumah Tangga Melalui DAGUSIBU dan Simulasi Kotak Obat Keluarga - Okta Muthia Sari; Aditya Maulana P.P; Arnida Arnida (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Management of drugs in households in the community is still high which is not appropriate in self-medication. This has the risk of having a negative impact on personal health and the environment. It is important for the public to have the correct knowledge regarding drugs. Therefore, the service team carried out service activities consisting of education and simulation of drug management in the household. This service aims to increase the knowledge and skills of the community regarding proper drug management. The method used in this service is through education (DAGUSIBU) and simulation (medicine box) in the management of household drugs. The service is carried out for the residents of Sungai Besar village, Banjar Regency, South Kalimantan. Service evaluation was carried out through filling out knowledge questionnaires and simulation observations. A total of 9 people participated in this service. The results of the evaluation using a questionnaire showed that after education and simulation there was an increase in the average knowledge of participants from 7.67 ± 1.414 to 11 ± 0 related to drug management in the household. In addition, the results of the observation evaluation showed that all participants (100%) were able to practice drug management in the household in the aspects of using, storing and disposing of drugs. By understanding and applying the correct way of managing drugs in the household, the goals of treatment can be achieved and do not cause environmental damage.